SARS-CoV-2: What we need to know and possible future therapies - Perlman, Stanley (Henry Stewart Talks, 2020)
SARS-COV-2 compared with other coronavirus strains, How this comparison can help in containment, treatment, and vaccination, Future considerations for vaccine development, Other possible treatments for COVID-19